2006
DOI: 10.1128/iai.00299-06
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Putative Virulence Factors of Escherichia coli O157:H7 Differs in Bovine and Human Infections

Abstract: Escherichia coli O157:H7 is a commensal organism in cattle, but it is a pathogen in humans. This differential expression of virulence suggests that specific virulence factors are regulated differently in human and bovine hosts. To test this hypothesis, relative real-time reverse transcription-PCR was used to relate the expression of several putative virulence genes (eae, espA, stx 2 , rfbE, ehxA, and iha) to that of the "housekeeping" gene gnd during natural human and experimental bovine infection with E. coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 43 publications
2
48
0
Order By: Relevance
“…In contrast, Shiga toxins cannot enter the general circulation in cattle as they lack vascular receptors (Valdivieso-Garcia et al 1996) thereby preventing the development of disease. Evidence provided by Rashid et al (2006) indicated that Shiga toxins are equally expressed in EHEC O157:H7-challenged cattle and humans suggesting that these toxins could have an impact on intestinal mucosa from cattle. Shiga toxins and other cytotoxins are toxic to epithelial cell lines, primary cultures of animal cells in vitro and intestinal organ cultures (Konowalchuk et al 1977;Sjogren et al 1994;Bauer and Welch 1996;Valdivieso-Garcia et al 1996;Schuller et al 2004;Aldick et al 2007).…”
Section: Ivoc Adherence Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Shiga toxins cannot enter the general circulation in cattle as they lack vascular receptors (Valdivieso-Garcia et al 1996) thereby preventing the development of disease. Evidence provided by Rashid et al (2006) indicated that Shiga toxins are equally expressed in EHEC O157:H7-challenged cattle and humans suggesting that these toxins could have an impact on intestinal mucosa from cattle. Shiga toxins and other cytotoxins are toxic to epithelial cell lines, primary cultures of animal cells in vitro and intestinal organ cultures (Konowalchuk et al 1977;Sjogren et al 1994;Bauer and Welch 1996;Valdivieso-Garcia et al 1996;Schuller et al 2004;Aldick et al 2007).…”
Section: Ivoc Adherence Assaymentioning
confidence: 99%
“…The current model for EHEC O157:H7 colonization in cattle suggests that the lymphoid-follicle dense mucosa in the terminal rectum is the primary colonization site and it is this colonization that is responsible for persistent shedding (Naylor et al 2003Sheng et al 2004Sheng et al , 2006Lim et al 2007). The basic assumption of this model is that cattle are not adversely affected by EHEC O157:H7 virulence factors, and although a reduction in the expression of some EHEC O157:H7 virulence factors has been demonstrated (Rashid et al 2006), it is not true for all virulence factors. For example, Rashid et al (2006) determined that Shiga toxins were expressed equally in humans and cattle, suggesting that these toxins play a similar role in both systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following preparation of this manuscript, Leveille et al reported that Iha of the uropathogen UCB34 is regulated by iron availability [9]. Finally, we have recently identified iha expression in E. coli O157:H7 in stools that have been freshly shed by infected children and experimentally inoculated cattle [17].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that specific type III effector molecules are required for the formation of classic attaching and effacing lesions in calves (Cookson and Woodward 2003); however, not all colonization is associated with the formation of actin pedestals (Vlisidou et al 2006). In addition, EHEC O157:H7 actin pedestals do not have the same appearance in cattle as those in disease-susceptible animals (Dibb-Fuller et al 2001), and a recent study suggests that this is attributable to lower expression of type III effector molecules in cattle (Rashid et al 2006). In contrast, Rashid et al (2006) determined that Shiga toxin expression is not different for human and cattle systems suggesting that cytotoxins could play a similar role in both systems.…”
mentioning
confidence: 72%